Estudo clínico comparativo da ação de géis clareadores de consultório sobre a estabilidade de cor e sensibilidade dentária - Abrantes, Priscila Silva (2019)
PURPOSE: to evaluate the efficacy, color stability and tooth sensitivity generated by a product based on 35% hydrogen peroxide and 37% carbamide peroxide in the dental office whitening technique. MATERIALS AND METHODS: This is a controlled, randomized, double-blind, split-mouth, 6-month follow-up clinical trial. Forty-one volunteers participated in two groups, G1 (control group) side that used hydrogen peroxide at 35% and G2 (experimental group) side that used 37% carbamide peroxide. The volunteers underwent three bleaching sessions with 35% hydrogen peroxide and 37% carbamide peroxide with a single application of 40 minutes for each gel, on their respective side of application and seven days interval between each session. Sensitivity values were obtained with the visual analog pain scale. Color was measured before and after each bleaching session. Statistical analysis was performed using paired Student T tests and ANOVA 2 factors with Tukey post test. RESULTS: Hydrogen peroxide presented an immediate global sensitivity of 6 times higher when compared to carbamide peroxide. For both gels, the color stability was maintained after 3 and 6 months. CONCLUSION: Dental bleaching in the office using 37% carbamide peroxide resulted in a lower dental sensitivity, without compromising clinical efficacy related to color and stability in the period of 3 and 6 months, when compared to 35% hydrogen peroxide.